Exploring the Role of the ATRX Gene in High-Risk Neuroblastoma via Genome Engineering Techniques - Jafargholizadeh, Setareh (My University, 2023)
Neuroblastoma (NB) is a rare but aggressive pediatric cancer originating form the embryonic neural crest cells. Abnormal telomere maintenance has been implicated as a major cause of high-risk neuroblastoma, with a subset of tumors following the Alternative Lengthening of Telomere positive (ALT+) pathway. ALT+ tumors are difficult to treat due to their resistance to therapy. The exact cause of NB remains unclear, but recent research suggests genetic mutations as a possible cause, particularly mutations in the ATRX gene observed in ALT+ NB patients. This study focuses on understanding the role of the ATRX gene, in promoting ALT+ neuroblastoma. To investigate this, a dual approach was utilized, involving CRISPR/Cas9 technology for complete ATRX knockout and lentiviral shRNA silencing to reduce ATRX expression. The gene expression of ATRX has been successfully downregulated, but the successful knockout of ATRX could not be verified using CRISPR/Cas9 methods. Hence, additional validation is necessary to assess the impact of ATRX expression on ALT+ and to develop more effective strategies for addressing this subgroup of high-risk neuroblastoma (NB).
Keywords: Neuroblastoma; Lentiviral vector; ATRX; CRISPR/Cas9